COVID-19 Influenced the Epidemiology of Facial Trauma: A Narrative Review, 2020–2024 - Gary R. Hoffman; Sophie K. M. Kelly (COVID)
The implementation of a range of social distancing and lockdown measures during the COVID-19 pandemic were seen to impact on the well-established epidemiology of facial trauma. This narrative review aimed to synthesize the international findings of this effect by evaluating the previously published literature. Relevant studies published between 1 January 2020, and 31 December 2024, were identified using four databases: PubMed, Embase, Cochrane, and SAGE Journals. A total of 63 studies across 19 countries were included. Descriptive analysis found that these were predominantly undertaken within oral and maxillofacial surgery departments (n = 48), as a single-center cohort study (n = 56), including greater than 500 patients (n = 22), with a duration of study between 1 and 52 weeks (n = 52). The principal finding was that 83% (n = 52) of studies reported a significant decrease in the number of facial trauma presentations. Falls (n = 35) in a domestic setting (n = 13) were identified, respectively, as the predominant etiology and place of injury. This is an out-of-the-ordinary observation when compared to routinely encountered causes. This study demonstrated that social distancing measures significantly influenced the epidemiology of facial trauma presentations that occurred during the pandemic.